Cost of carry, financial constraints, and dynamics of corporate cash holdings - Eskandari, Ruhollah; Zamanian, Morteza (Journal of Corporate Finance, 2022)
This paper provides new evidence on how the cost of carry is linked to corporate cash policy in the presence of financial frictions. Using both time-series and firm-level data for US public and private manufacturing firms, we find a negative correlation between cash holdings and the cost of carry for financially unconstrained firms. We find no evidence of such a relation for financially constrained firms. Our results suggest that financial constraints play an important role in adjusting cash to changes in the cost of carry. We introduce a simple model in which firms differ in their cost function of external finance, where the constrained firms' highly curved cost function drives a steeper cash demand, leading to their lower cash sensitivity to the cost of carry.